Nitrogen Balance During Venovenous Extracorporeal Membrane Oxygenation Support: Preliminary Results of a Prospective, Observational Study. Issue 3 (25th May 2018) - Pelekhaty, Stacy; Galvagno, Samuel M.; Hochberg, Eric; Herr, Daniel L.; Lantry, James H.; Kon, Zachary N.; Deatrick, Kristopher B.; Menaker, Jay
Abstract: Background: Current literature is insufficient to support specific guidelines for estimating nutrition needs during extracorporeal membrane oxygenation (ECMO). The purpose of this single‐center observational study was to investigate protein catabolism during venovenous (VV) ECMO support and assess whether current nutrition recommendations were adequate. Methods: All patients admitted to the Lung Rescue Unit between November 2016 and June 2017 were screened for eligibility. Patients with a documented nitrogen balance (NB) study were included in the data set. NB results were excluded for a change in blood urea nitrogen ≥10 mg/dL during the urine collection or unquantified nitrogen losses. Demographics, ECMO‐specific data, NB, nutrition prescription, and infusion were recorded in a prospective, observational manner. Results: After exclusions, 25 NB results in 16 patients were included for analysis. Nonobese (body mass index [BMI] ˂ 30 kg/m 2 ) and obese (BMI ≥ 30 kg/m 2 ) patients received 85% and 84% of their prescribed protein, respectively. Nonobese patients had a mean NB of −1.7 ± 5.7, whereas obese patients had a mean NB of −11.5 ± 9.6. Obese patients displayed significantly higher urine urea nitrogen (26.7 ± 7.7 vs 13.5 ± 4.3; P = .00004). Conclusions: These preliminary findings suggest that current guidelines for estimating protein needs in critically ill patients may be adequate for nonobese patients receiving VV ECMO. However, current protein recommendations for critically ill obese patients may not be adequate during VV ECMO support, possibly related to significantly higher rates of catabolism. Future studies with a larger cohort of patients are needed to confirm these results.